Unlocking Unlocking the Sustainable Development Goals with Public Private Partnership and Local Government Role: Insights from Pakistan - Tabbasum, Sidra; Hussain, Anwar; Husnain Shah, Syed; Irfan Aslam, Hafiz Shahid (Journal of Public Policy Practitioners, 2025)
This research paper intends to elaborate on the part that the local administrations have in seizing the public-private partnership (PPPs) opportunities through the execution of the SDGs in Pakistan. This study is conducted with systematic literature review approach to analysis the role of PPPs and the local government. For this purpose, the study collected 500 research manuscripts from Elesvier, Taylor and francis, Emerlad, ABDC and Web of Science journal, and selected 206 to analyze the PPPs and the local government’s role. It is observed from synthesis analysis that the local government’s role is a key factor for the success of PPPs in Pakistan. In addition, political uncertainity, involvement and transparency are key hurdles to achieve SDGs in Pakisan. Out of these analysis, this research recommends to re-draft policy, strategies and the need to retransform digital governance to achieve successful PPPs with the help of local government role. These solutions could play an important role toward SDGs achievement in Pakistan.